In Nagaland... Entrepreneurial start-up through beekeeping - Singh, A K; Singh, Rudra P (Indian Horticulture, 2019)
Beekeeping is going to be an enthralling occupation to the tribal people for employment and income with low cost input. Being a most benign and sustainable enterprise, it is now recognized as an important entrepreneurial venture or start-up in the tribal community to curtail the people’s migration from their area and ultimately uplifts the tribal livelihood in Nagaland. In Nagaland, most of the beekeepers are harvesting only limited beehive products, viz. honey and wax, which is meager as compared to all other advantages of apiculture. This industry is now providing many beehive products, viz. honey, wax, propolis, bee venom, royal jelly and pollen along with a natural device in form of pollination services for cross pollinated crops. Mostly, tribal populations rear honeybee for production of honey because traditionally they are partially dependent on honey collection from wild sources for their income and their perception too is that, beekeeping provides only honey. In addition, beehive products contribute important ingredients of traditional medicines. Only a few small-scale beekeepers are producing honey for their personal consumption and a sizeable volume is sold in local market where their average productivity of honey is 2-3 kg/hive.